Effects of Color Attributes on Trap Capture Rates of Chrysobothris femorata (Coleoptera: Buprestidae) and Related Species. Issue 4 (28th June 2022) - Perkovich, Cynthia L; Addesso, Karla M; Basham, Joshua P; Fare, Donna C; Youssef, Nadeer N; Oliver, Jason B
Abstract: Chrysobothris spp. (Coleoptera: Buprestidae) and other closely related buprestids are common pests of fruit, shade, and nut trees in the United States. Many Chrysobothris spp., including Chrysobothris femorata, are polyphagous herbivores. Their wide host range leads to the destruction of numerous tree species in nurseries and orchards. Although problems caused by Chrysobothris are well known, there are no reliable monitoring methods to estimate local populations before substantial damage occurs. Other buprestid populations have been effectively estimated using colored sticky traps to capture beetles. However, the attraction of Chrysobothris to specific color attributes has not been directly assessed. A multi-color trapping system was utilized to determine color attraction of Chrysobothris spp. Specific color attributes (lightness [ L *], red to green [ a *], blue to yellow [ b *], chroma [ C *], hue [ h *], and peak reflectance [ PR ]) were then evaluated to determine beetle responses. In initial experiments with mostly primary colors, Chrysobothris were most attracted to traps with red coloration. Thus, additional experiments were performed using a range of trap colors with red reflectance values. Among these red reflectance colors, it was determined that the violet range of the electromagnetic spectrum had greater attractance to Chrysobothris. Additionally, Chrysobothris attraction correlated with hue and b*, suggesting a preference for traps with hues between red to blue. However, males and females of some Chrysobothris species showed differentiated responses. These findings provide information on visual stimulants that can be used in Chrysobothris trapping and management. Furthermore, this information can be used in conjunction with ecological theory to understand host-location methods of Chrysobothris .